Immunological Interfaces: The COVID-19 Pandemic and Depression - Perlmutter, Austin (Frontiers in Neurology, 2021)
Since the start of the spread of the coronavirus disease 2019 (COVID-19), an international effort has sought to better characterize associated extra-pulmonary health sequelae. The acute and or chronic detrimental impact of SARS-CoV-2 infection on mental health, especially depression, is increasingly described. Simultaneously the pandemic has influenced depressive symptomatology by modifying economic, social and political structures, in addition to affecting daily routines. In both cases, associated immunological perturbations favoring a pro-inflammatory state could underlie an increased risk for depressive symptomatology. A resultant elevation in global depressive burden could further tax mental health care infrastructure and contribute to a range of worse health outcomes including diminished quality of life. This suggests a critical and time-sensitive need to better understand immune interfaces between depression and COVID-19.